Total Quality and Total Mobility - Trieste, Giuseppe; de Mitri, Daniela (TeMA - Journal of Land Use, Mobility and Environment, 2010)
FIABA ONLUS (Italian Fund for Elimination of Architectural Barriers) was founded in 2000 with the aim of promoting a culture of equal opportunities and, above all, it has as its main goal to involve public and private institutions to create a really accessible and usable environment for everyone. Total accessibility, Total usability and Total mobility are key indicators to define quality of life within cities. A supportive environment that is free of architectural, cultural and psychological barriers allows everyone to live with ease and universality. In fact, people who access to goods and services in the urban context can use to their advantage time and space, so they can do their activities and can maintain relationships that are deemed significant for their social life. The main aim of urban accessibility is to raise the comfort of space for citizens, eliminating all barriers that discriminate people, and prevent from an equality of opportunity. “FIABA FUND - City of ... for the removal of architectural barriers” is an idea of FIABA that has already affected many regions of Italy as Lazio, Lombardy, Campania, Abruzzi and Calabria. It is a National project which provides for opening a bank account in the cities of referring, in which for the first time, all together, individuals and private and public institutions can make a donation to fund initiatives for the removal of architectural barriers within its own territory for a real and effective total accessibility. Last February the fund was launched in Rome with the aim of achieving a Capital without barriers and a Town European model of accessibility and usability. Urban mobility is a prerequisite to access to goods and services, and to organize activities related to daily life. FIABA promotes the concept of sustainable mobility for all, supported by the European Commission’s White Paper. We need a cultural change in management and organization of public means, which might focus on individual in its totality, with all its needs. For this reason it is necessary to focus on output of public and private transports which must be totally and globally accessible. Metropolitan and suburban transports need to have modern buses, and it has been calculated that it is possible to provide a total replacement of the fleet in a period from five to ten years. Total Quality must become the goal of every Local Government. FIABA suggests that a Total Quality Manager be always present in the institutional environment, as a guarantor of quality perceived by people living in their city for tourism, work, and leisure. It is essential to establish a favorable environment for all, to ensure the comfort of 100% of the population to give some definite and reliable answers.